1996
DOI: 10.1677/joe.0.1480103
|View full text |Cite
|
Sign up to set email alerts
|

Pig uterine luminal fluid contains the developmentally regulated neurotrophic factor, pleiotrophin

Abstract: The pig conceptus produces a non-invasive placenta which is probably dependent on uterine secretory products during both the pre- and post-attachment periods. Since some of these factors are also produced during the oestrous cycle, uterine luminal flushings (ULF) from adult nonpregnant pigs were analysed to identify potentially important maternally-secreted growth factors or cytokines. ULF contained several proteins that were detected on Western blots by an antibody raised against the N-terminal 14 amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Although we have previously shown that constituent growth factors in this cationic extract include PDGF, HB-EGF, bFGF, and PTN (2,8,12), heparin affinity chromatography revealed the presence of an additional unidentified HBGF that required 0.8 M NaCl for elution from an EconoPac heparin column and, in terms of the amount of bioactivity recovered from the column, appeared to be a principal cationic HBGF in ULF for 3T3 cells (Fig. 1A).…”
Section: Characterization and Purification Of An Atypical Hbgf In Ulf-mentioning
confidence: 75%
See 2 more Smart Citations
“…Although we have previously shown that constituent growth factors in this cationic extract include PDGF, HB-EGF, bFGF, and PTN (2,8,12), heparin affinity chromatography revealed the presence of an additional unidentified HBGF that required 0.8 M NaCl for elution from an EconoPac heparin column and, in terms of the amount of bioactivity recovered from the column, appeared to be a principal cationic HBGF in ULF for 3T3 cells (Fig. 1A).…”
Section: Characterization and Purification Of An Atypical Hbgf In Ulf-mentioning
confidence: 75%
“…Although the presence of CTGF-like activity in uterine flushings was initially demonstrated several years ago (2,8,38), its identification and structural characterization was not possible until the development of the purification protocol described herein, which allowed for its separation from other unrelated HBGFs such as PDGF, bFGF, HB-EGF, and PTN (2,8,12). The data presented in this report show that a fibroblast and smooth muscle cell growth factor in uterine secretory fluids is a CTGF protein that is heparin-binding and substantially N-terminally truncated in comparison with the predicted CTGF primary translation product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these ligands are expressed by the pig endometrium during early pregnancy (Brigstock et al, 1990(Brigstock et al, , 1996a(Brigstock et al, , 1996bKennedy et al, 1994;Kim et al, 1995). A quantitative trait locus (QTL) for uterine capacity was identified on the long arm of chromosome 8 near 71 cM .…”
Section: Copyright © 2002 S Karger Ag Baselmentioning
confidence: 99%
“…Recent studies suggest that, during development, HARP is involved in stroma-epithelium interactions (Vanderwinden et al 1992, Mitsiadis et al 1995b and in growth and cell differentiation steps (Peng et al 1995, Szabat & Rauvala 1996. HARP has been isolated from adult brain (Courty et al 1991), follicular fluid (Ohyama et al 1994), mature uterus (Milner et al 1989) and uterine luminal fluid (Brigstock et al 1996). In addition, HARP mRNA is upregulated by androgens in cultured prostatic epithelial cells .…”
Section: Introductionmentioning
confidence: 99%